Andreas Hills Condominiums Award of Excellence, 1973 - The Island California Chapter of the American Institute of Architects::::::::: (1973)
An Award of Excellence for the Andreas Hills Condominiums designed by William F. Cody, awarded by the Inland California Chapter of the American Institute of Architects, dated December 19th, 1973.